Three-component synthesis of highly functionalized aziridines containing a peptide side chain and their one-step transformation into β-functionalized α-ketoamides - Huck, Lena; González, Juan F.; de la Cuesta, Elena; Menéndez, J. Carlos (Beilstein Journal of Organic Chemistry, 2016)
A sequential three-component process is described, starting from 3-arylmethylene-2,5-piperazinediones and involving a one-pot sequence of reactions achieving regioselective opening of the 2,5-diketopiperazine ring and diastereoselective generation of an aziridine ring. This method allows the preparation of N-unprotected, trisubstituted aziridines bearing a peptide side chain under mild conditions. Their transformation into β-trifluoroacetamido-α-ketoamide and α,β-diketoamide frameworks was also achieved in a single step.
Keywords: α-ketoamides; aziridines; multicomponent reactions; nitrogen heterocycles; one-pot reactions; peptide mimics; vicinal tricarbonyl compounds

Medicinal Chemistry of Anticancer Drugs - Avendaño, C.; Menéndez, J. C. (DNA Alkylating Agents, 2015)

(untitled) - Roxin, Á.; Chen, J.; Scully, C. C. G.; Rotstein, B. H.; Yudin, A. K.; Zheng, G. (Bioconjugate Chem., 2012)

(untitled) - Dyer, F. B.; Park, C.-M.; Joseph, R.; Garner, P. (J. Am. Chem. Soc., 2011)

(untitled) - Diaper, C. M.; Sutherland, A.; Pillai, B.; James, M. N. G.; Semchuk, P.; Blanchard, J. S.; Vederas, J. C. (Org. Biomol. Chem., 2005)

(untitled) - Galonić, D. P.; Ide, N. D.; van der Donk, W. A.; Gin, D. Y. (J. Am. Chem. Soc., 2005)

(untitled) - Lin, C.; Kwong, A. D.; Perni, R. B. (Infect. Disord.: Drug Targets, 2006)

(untitled) - Njoroge, F. G.; Chen, K. X.; Shih, N.-Y.; Piwinski, J. J. (Acc. Chem. Res., 2008)

(untitled) - Ibuka, T. (Chem. Soc. Rev., 1998)

(untitled) - Pellissier, H. (Tetrahedron, 2010)

Aziridines and epoxides in organic synthesis - Yudin, A. K. (Wiley-VCH, 2006)

(untitled) - Sweeney, J. B. (Chem. Soc. Rev., 2002)

(untitled) - Jenkins, D. M. (Synlett, 2012)

(untitled) - Jung, N.; Bräse, S. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hashimoto, T.; Nakatsu, H.; Yamamoto, K.; Maruoka, K. (J. Am. Chem. Soc., 2011)

(untitled) - Künzi, S. A.; Morandi, B.; Carreira, E. M. (Org. Lett., 2012)

(untitled) - Davis, F. A.; Deng, J. (Org. Lett., 2007)

(untitled) - Baumann, M.; Baxendale, I. (Synlett, 2016)

(untitled) - González, J. F.; Ortín, I.; de la Cuesta, E.; Menéndez, J. C. (Chem. Soc. Rev., 2012)

(untitled) - Borthwick, A. D. (Chem. Rev., 2012)

(untitled) - González, J. F.; de la Cuesta, E.; Avendaño, C. (Tetrahedron, 2008)

(untitled) - Bull, S. D.; Davies, S. G.; Garner, A. C.; O’Shea, M. O. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Farran, D.; Echalier, D.; Martínez, J.; Dewynter, G. (J. Pept. Sci., 2009)

(untitled) - Kher, S.; Jirgensons, A. (Curr. Org. Chem., 2014)

(untitled) - Bartels, A.; Jones, P. G.; Liebscher, J. (Synthesis, 2003)

(untitled) - Florio, S.; Luisi, R. (Chem. Rev., 2010)

(untitled) - Krake, S. H.; Bergmeier, S. C. (Tetrahedron, 2010)

Heterocycles in Natural Product Synthesis - Botuha, C.; Chemla, F.; Ferreira, F.; Pérez-Luna, A. (Aziridines in Natural Product Synthesis, 2011)

(untitled) - Stanković, S.; D’hooghe, M.; Catak, S.; Eum, H.; Waroquier, M.; Van Speybroeck, V.; De Kimpe, N.; Ha, H.-J. (Chem. Soc. Rev., 2012)

(untitled) - Degennaro, L.; Trinchera, P.; Luisi, R. (Chem. Rev., 2014)

(untitled) - Kumar, M.; Gandhi, S.; Singh Kalra, S.; Singh, V. K. (Synth. Commun., 2008)

(untitled) - Wasserman, H. H.; Chen, J.-H.; Xia, M. (J. Am. Chem. Soc., 1999)

(untitled) - Rubin, M. B.; Gleiter, R. (Chem. Rev., 2000)

(untitled) - Wasserman, H. H.; Parr, J. (Acc. Chem. Res., 2004)